2005
DOI: 10.1590/s1678-77572005000400011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an oral health promotion program for infants in the public sector

Abstract: his study compared the caries index (dmft), presence of sucking habits and facial alterations in children attended by the preventive program for infants and children assisted by spontaneous demand, at the same age, at the public sector of Maringá, PR. A total of 100 children were evaluated (1-6 years), who were divided into 2 groups: GI -children attended by the infant program with educational and preventive care and bimonthly follow-up, since the 1 st year of age; GII -children assisted for conventional treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
2
13
0
3
Order By: Relevance
“…Several studies have identified an association between oral health and socioeconomic variables such as family income 9,12,20 , educational level 12,22 , delay and disruption of the education of the child 7 and social class 16,23,33 , in various locations including Australia 17 , New Zealand 28 , Jordan 29 , Japan 31 , Sweden 19 , the UK 10 and Brazil 8,11,27,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified an association between oral health and socioeconomic variables such as family income 9,12,20 , educational level 12,22 , delay and disruption of the education of the child 7 and social class 16,23,33 , in various locations including Australia 17 , New Zealand 28 , Jordan 29 , Japan 31 , Sweden 19 , the UK 10 and Brazil 8,11,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have addressed the correlation between oral health and social factors such as income, education, number of children, and other variables 12,16,21,22,25,31 . The national surveys conducted in Brazil in 2000 and 2010 showed that oral health is heterogenous, with differences found among regions and social groups.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Fracasso Mde et al . [13] and Wagner et al . [14] where mean dmft was less in the test group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo constatou-se uma baixa prevalência de cárie nas crianças com ceo-s médio (0,55±1,64), freqüentadoras do programa de atenção precoce do serviço público de saúde da cidade de Maringá-PR, semelhante aos dados encontrados em um outro trabalho realizado, com crianças de 1 a 5 anos atendidas neste mesmo programa 11 , bem como, aos resultados encontrados em outro estudo, com crianças de 0 a 36 meses 20 . Porém, inferior aos encontrados por outros autores [21][22][23][24][25] , considerando a cárie segundo os critérios da OMS.…”
Section: Discussionunclassified
“…A alta do atendimento é prevista para os 6 anos. Durante o período que as crianças permanecem em atendimento, recebem consultas bimestrais reforçando a necessidade de medidas preventi vas caseiras e profi ssionais regulares, bem como a necessidade de interpor medidas para interceptação de hábitos nocivos de dieta, higiene e de sucção não nutriti va, prevenindo desta forma aparecimento de lesões de cárie e maloclusões 11 . O processo da coleta de dados teve a parti cipação de 01 cirurgião-denti sta da Secretaria Municipal de Saúde do município de Maringá que roti neiramente é responsável pelo atendimento das crianças.…”
Section: Metodologiaunclassified